Treatment of Caries in the Upper Jaw Buttonhole Belt - Siddiqov Xotamjon Muminovich (Genius Journals, 2022)
Inflammatory complications are very often observed in patients with traumatic fractures of the lower jaw inside the teeth, and, according to some authors, there is a tendency to increase their number. One of the common causes of complications that occur both in the treatment of mandibular fractures and in the late and longer posttraumatic period is a tooth that has survived in the fracture plane.
Keywords: Caries infiltration, minimally invasive caries treatment, children, permanent teeth, trauma of the lower jaws